Indonesia's Foreign Policy : Suspends Sending Indonesian Migrant Workers (PMI) to Malaysia After the Establishment of the Online Maid System (SMO) by the Malaysian Government - Nurfarah Nidatya; Muhammad Kamil Ghiffary Abdurrahman; Dini Putri Saraswati (Universitas Serang Raya, 2023)
Indonesia stopped sending Indonesian migrant workers (PMI) to Malaysia after the establishment of the Online Maid System (SMO) by the Malaysian government. SMO created various issues for PMI, especially in protecting their rights. A qualitative method was used in this study. This study discusses various factors that underlying Indonesia's foreign policy to freeze on sending PMI to Malaysia in 2022 after the establishment of the Online Maid System (SMO) by the Malaysian Government. This foreign policy analysis used funnel of causality theory from Eugene Wittkopf. This study results showed that domestic and international factors influenced in formalizing foreign policy. Domestic factors affected Indonesia's foreign policy to freeze on sending of PMI to Malaysia in 2022 after the establishment of the Online Maid System (SMO) by the Malaysian Government, including the Indonesian government's policy regarding regulation and protection of the migrant workers rights. Similarly, the role and influence of community and human rights activists in Indonesia who struggled the rights and interests of Indonesian migrant workers. The international factors, including global human rights issues for Indonesian Migrant Workers, Malaysia's policy in implementing the Online Maid System and bilateral relations between Indonesia and Malaysia related in sending PMI to Malaysia.